The public policy of access to land for Family Farming in Argentina. Historical becoming of a persistent issue - Mosca, Valeria Ana (Universidad Nacional del Litoral, 2022)
Through the review and systematization of specialized historical bibliography and information collected from the mass media and exploratory interviews, in this article we seek to identify and analyze the emergence and becoming of access to land of family farming as a 'question' throughout Argentine history. In line with our analytical theoretical perspective on public policy, which is based on the social process that is orchestrated around a “socially problematized issue”, we set ourselves this objective. We conclude that it is a problem whose origin dates back to the founding moments of the Argentine nation-state and therefore we carry out a historical review. In this sense, we consider that it is a matter historically problematized by the family farming sector in Argentina.